Pernikahan dalam Keadaan Ihram: Analisis Fikih Munakahat Mazhab Hanafi - Imam Faishol (Mutawasith: Jurnal Hukum Islam, 2025)
This research is motivated by the contradiction of hadiths regarding the law of marriage contracts during ihram, which results in a sharp difference of opinion between the majority of scholars (who forbid it) and the Hanafi School (which permits it). The study aims to fundamentally analyze the internal arguments of the Hanafi School regarding this permissibility, focusing on linguistic aspects (wording), qiyas methods, and sanad criticism. This research uses a normative-textual qualitative method through a literature review of primary Hanafi fiqh books such as al-Hidayah and al-Mabsuth. The findings reveal that the permissibility in the Hanafi School is based on a conceptual distinction between the contract (aqd) and sexual intercourse (jima'), where the prohibition in the texts is interpreted as applying only to physical relations, not to the contractual transaction. This conclusion is supported by three main pillars: linguistic interpretation of the term “nikah”, the application of qiyas equating a marriage contract with other civil contracts, and critical assessment of the hierarchy of evidence.